Desain dan Implementasi Aplikasi Steganografi Dual Mode Berbasis Java untuk Menyembunyikan Pesan Teks dan Gambar - Siti Sundari; Mauliza Vazira; Monica Annisa Fitri; Hafizah Hafizah (LEMBAGA KAJIAN PEMBANGUNAN PERTANIAN DAN LINGKUNGAN (LKPPL), 2026)
Steganography is a method of protecting information by hiding secret messages within a carrier medium, making their presence difficult for others to detect. This research aims to design and build a Java-based dual-mode steganography application that can hide text messages within text (text-to-text) and image messages within text (text-to-image). This application was created using the Java programming language with an object-oriented programming approach, and utilizes the Base64 encoding technique as a means of embedding data. The research methods applied included requirements analysis, system design, implementation, and application testing. The test results demonstrated that this application can effectively hide and extract text messages and images, while using a password as an additional layer of security. We hope this application can be a practical solution for maintaining the confidentiality of digital data, while also serving as a useful steganography learning tool for students.